A flow-rate-controlled double-nozzles approach for electrochemical additive manufacturing. Issue 1 (2nd January 2022) - Guo, Yawen; Liu, Pengpeng; Jiang, Pengfei; Hua, Yongshuai; Shi, Kaiyuan; Zheng, Hui; Yang, Yabin
ABSTRACT: The electrochemical additive manufacturing technique based on the meniscus-confined approach has been proved to be a powerful tool for fabricating nanoscale and microscale metal components. The stability of the meniscus is the key in this meniscus-confined approach to achieve high resolution and reliable product quality. In the present study, a double-nozzles design, which consists of a feed nozzle and a suction nozzle, is proposed for the meniscus confined electrochemical additive manufacturing technique. It was demonstrated that the proposed design possessed robust control of the stability of the meniscus by manipulating the feed and suction rates of the two nozzles in a quite large range. Various sizes of menisci can be easily obtained by utilising nozzles with different sizes. Compared with the pressure-controlled single-nozzle approach, the results showed that dense structures without dendrites can be fabricated by the double-nozzles design with larger current density due to the feed-and-suction process at the tip of the nozzles. The proposed flow-rate-controlled double-nozzles design was finally employed to fabricate some copper circuits and a Cu/CuNi thin film thermocouple to demonstrate its potential in fabricating electronic devices.